2015
DOI: 10.1017/s002966511500066x
|View full text |Cite
|
Sign up to set email alerts
|

The Livewell plate computer app: Development and testing of an interactive computer app balancing healthy and environmental aspects of food choice

Abstract: Addressing sustainability of the food system requires balancing of health, environmental, social and economic aspects of food choices. While we have shown that it is possible to create a realistic diet that can achieve both dietary requirements for health and have a lower environmental impact in terms of reducing greenhouse gas emissions (GHGE) (1) , it is difficult to communicate to the public how to balance these concerns in everyday food choices. The aim of this study was to develop and test an educational … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 1 publication
0
7
0
Order By: Relevance
“…– the rules directly focus on environmental or social aspects of sustainability, for example:Eat better food (Sustain; a British NGO)/Buy food that meets a credible certified standard; consider MSC, free-range and fair trade (WWF)/Organic foods and fair trade products (Germany)/Value your food, ask where it comes from and how it is produced (UK)/Choose fish sourced from sustainable stocks, seasonality and capture methods are important here too (UK);Seasonal and regional – your first choice (Germany)/Buy local, seasonal and environmentally friendly food (Sustain)/Urban, rural, regional – sustainable farming with short transport routes and seasonal products (Germany);Drink tap water (UK)/Tap water is the drink with the lowest environmental impact (Sweden)/Tap water is drinking-water (Germany);Waste less food (WWF)/Aim to be waste-free: reducing food waste and packaging (Sustain)/Don’t waste food (UK) ( 10 , 17 – 22 ) .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…– the rules directly focus on environmental or social aspects of sustainability, for example:Eat better food (Sustain; a British NGO)/Buy food that meets a credible certified standard; consider MSC, free-range and fair trade (WWF)/Organic foods and fair trade products (Germany)/Value your food, ask where it comes from and how it is produced (UK)/Choose fish sourced from sustainable stocks, seasonality and capture methods are important here too (UK);Seasonal and regional – your first choice (Germany)/Buy local, seasonal and environmentally friendly food (Sustain)/Urban, rural, regional – sustainable farming with short transport routes and seasonal products (Germany);Drink tap water (UK)/Tap water is the drink with the lowest environmental impact (Sweden)/Tap water is drinking-water (Germany);Waste less food (WWF)/Aim to be waste-free: reducing food waste and packaging (Sustain)/Don’t waste food (UK) ( 10 , 17 – 22 ) .…”
mentioning
confidence: 99%
“…Waste less food (WWF)/Aim to be waste-free: reducing food waste and packaging (Sustain)/Don’t waste food (UK) ( 10 , 17 – 22 ) .…”
mentioning
confidence: 99%
“…Typically, food drives 20–30 % of the life-cycle environmental impacts of final household consumption ( 5 ) . To reduce the current burden of food consumption on the environment, food consumption patterns need to change ( 6 , 7 ) .…”
mentioning
confidence: 99%
“…Previous literature has shown that changing the sources of food will not be adequate to meet the current GHGE targets set by the UK Government and there is a need to shift diets towards more sustainable diets. 8 35 Our analysis suggests that with regard to one environmental indicator—GHGEs—implementation of the SFP will not lead to a more sustainable diet and could lead to increases in emissions.…”
Section: Discussionmentioning
confidence: 95%